2011
DOI: 10.1093/cid/cir442
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Respiratory Hospitalizations During Influenza Seasons in Ontario, Canada: A Cohort Study

Abstract: Evidence from the 2009 H1N1 pandemic suggests that severe obesity was a risk factor for serious complications from influenza infection. Our study identifies severe obesity as a risk factor for respiratory hospitalizations during seasonal influenza epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(166 citation statements)
references
References 21 publications
7
152
2
5
Order By: Relevance
“…Based on multivariate regression analysis, obesity was independently associated with ICU admission and therefore the occurrence of severe disease. These findings were consistent with the results of previous studies (15,16).…”
Section: Discussionsupporting
confidence: 94%
“…Based on multivariate regression analysis, obesity was independently associated with ICU admission and therefore the occurrence of severe disease. These findings were consistent with the results of previous studies (15,16).…”
Section: Discussionsupporting
confidence: 94%
“…One recent study of the NHANES cohort found a consistent association between obesity and pH1N1 hospitalisations/death, after stratifying by comorbidity, suggesting a true diathesis [34]. In the seasonal influenza literature, Kwong et al have demonstrated an association between obesity and increased respiratory hospitalisations, after adjusting for diabetes and cardiovascular disease [37]. Obesity may therefore account for the association between diabetes and influenzaattributable illness to an unknown extent [38].…”
Section: Discussionmentioning
confidence: 99%
“…Death was associated with both obesity, defined as BMI ≥30 (OR: 3.1; 95% CI = 1.5-6.6) and extreme obesity (OR: 7.6; 95% CI = 2.1-27.9). A Canadian cohort study covering 12 seasons (1996-97 through 2007-08) found that persons with a BMI of 30.0-34.9 and those with a BMI ≥35 were more likely than normal-weight persons to have a respiratory hospitalization during influenza seasons (OR: 1.45; 95% CI = 1.03-2.05 for BMI 30-34.9 and OR: 2.12; 95% CI = 1.45-3.10 for BMI ≥35) (85). Conversely, a two-season study in the United States found no association between obesity and medically attended LCI, including both seasonal and pandemic virus circulation (86).…”
Section: Persons With Increased Risk For Severe Influenza Illness Andmentioning
confidence: 99%